(untitled) (KYAMC Journal, 2017)
The aim of this study was to find out the adhesion formation after closing of parietal peritoneum at primary caesarean section done in different indications; the patients were admitted in Khwaja Yunus Ali Medical College & Hospital, a rural tertiary hospital in Bangladesh. In this study total 872 pregnant women were evaluated in 4 years period, who were admitted either from OPD or through emergency. Most of the caesarean sections were done due to elective causes. After the primary caesarean section, the repeat caesarean section was done in the same hospital by same surgeon within these time period and observed that there was no or few filmy adhesions were formed. So it was evaluated that, objectively to accept this step that is peritoneal closure in our operation procedure to reduce peritoneal adhesion formation. KYAMC Journal Vol. 6, No.-2, Jan 2016, Page 627-630